Pengelolaan Dan Pemanfaatan Tanah Kas Desa Oleh Perangkat Desa (Ex-Tanah Bengkok)(Studi Kasus di Desa Kandangan Kecamatan Ngawi Kabupaten Ngawi) - Dewi, Lavellia Ardita, Darsono, S.H., M.Hum (2017)
The purpose of this study is to understand suitability an implementation management and utilization of ground the village treasury as allowance for village government to applicable regulation. To understand auction stages of ground the village treasury by village government to village community. In this study to use a empirical juridical's methods. Management and utilization of ground the village treasury in Indonesia should be based on the principles in the regulations, that is The Principle of Public Interest; Fungsional Principle; The Principle of Legal Certainty; The Principle of Openness; The Principle Effectiveness; The Principle of Accountability; Certainty Principle of Economic Value. The Auction of ground the village treasury by village government should be done to openly and to known to the villagers widely.